2023
DOI: 10.1039/d3tb01186k
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the power of polyol-based polyesters for biomedical innovations: synthesis, properties, and biodegradation

Vafa Fakhri,
Chia-Hung Su,
Masoud Tavakoli Dare
et al.

Abstract: Polyesters based on polyols have emerged as promising biomaterials for various biomedical applications, such as tissue engineering, drug delivery systems, and regenerative medicine, due to their biocompatibility, biodegradability, and versatile...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 233 publications
(316 reference statements)
0
5
0
Order By: Relevance
“…The findings of this research, in comparison to other articles, demonstrate that, unlike polymers with a single degradation rate, it is achievable to attain the adjusted degradation rate through blending while maintaining suitable properties. 5,9,17 In other studies, it has been observed that adjusting the crosslink density, using different monomers, and blending with incompatible polymers are methods used to control the degradation rate. However, these modifications lead to reduced biocompatibility and affect the physical and mechanical properties.…”
Section: In Vitro Degradation Characterizementioning
confidence: 99%
See 3 more Smart Citations
“…The findings of this research, in comparison to other articles, demonstrate that, unlike polymers with a single degradation rate, it is achievable to attain the adjusted degradation rate through blending while maintaining suitable properties. 5,9,17 In other studies, it has been observed that adjusting the crosslink density, using different monomers, and blending with incompatible polymers are methods used to control the degradation rate. However, these modifications lead to reduced biocompatibility and affect the physical and mechanical properties.…”
Section: In Vitro Degradation Characterizementioning
confidence: 99%
“…These features make them well-suited for tissue engineering and drug delivery purposes. [4][5][6][7] However, it is important to note that PPS bioelastomers are not ideal for long-term applications and may require modifications to their properties for tissue engineering purposes. [8][9][10][11] PPA bioelastomers offer properties similar to PPS polymers for tissue engineering applications, but these polymers have certain limitations too that must be considered.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to their sustainability, plant oils are both cost‐effective and widely available on a global scale. Over the past decade, the utilization of plant oils as eco‐friendly raw materials for the synthesis of biopolymers has garnered considerable attention within the scientific community 29 . Among the plant oil family, soybean oil and its derivatives stand out as some of the most accessible and well‐regarded members, with recent research exploring their applications in areas such as bioinks, 30 green composites, 31 bio‐based coatings, 32 and autonomous self‐healing materials 33 .…”
Section: Introductionmentioning
confidence: 99%